TANTANGAN GURU DALAM MENGHADAPI PERUBAHAN KURIKULUM MERDEKA MENUJU PEMBELAJARAN MENDALAM DI SEKOLAH DASAR - hasnipindah12 Irga (Jurnal Dharma PGSD, 2026)
The transition from the 2013 Curriculum to the Kurikulum Merdeka (Emancipated Curriculum) which is oriented toward the "Deep Learning" paradigm presents tangible challenges for elementary school teachers. This study aims to identify the primary challenges teachers face in implementing this shift, particularly within the context of deep learning, which emphasizes meaningful conceptual mastery, critical thinking, and active student engagement. A descriptive qualitative method was employed, utilizing in-depth interviews with twenty teachers of grades 4, 5, and 6 from ten public elementary schools in Dharmasraya Regency, West Sumatra Province, selected via purposive sampling. Data were analyzed using the Miles and Huberman model. The findings reveal four dominant challenges: (1) teachers' limited conceptual understanding of the deep learning philosophy; (2) difficulties in designing authentic assessments that go beyond rote memorization; (3) administrative burdens that hinder pedagogical creativity; and (4) a lack of infrastructure support and continuous professional training. The study concludes that the success of the curriculum transition relies heavily on teacher capacity and systemic support from both schools and local government. Recommendations include strengthening school-based professional development programs and streamlining teachers' administrative workloads.